Sahelian Languages, Indigenous Knowledge and Self-Management - Easton, Peter (World Bank, Washington, DC, 2012)
While many of the languages in Africa may be related, and inter-comprehensible, it is also a multilingual continent, where a relatively high proportion of the population speaks, or understands more than one language. However, the distribution of languages is not uniform. The reasons are both topographical, and political: dense forests, numerous, rivers, thus hampering both transport, and communications. The note identifies the work of a local nongovernmental organization, established by community members to prod literacy instruction centers in West Africa. Primary education completion exams - which must be taken in French, and govern admission to secondary schooling, reveal that children who started education in their mother tongue, performed on average, significantly better than graduates of standard primary schools. The note further examines case studies in different countries, revealing this change is most pronounced in Francophone countries, where little recognition was given to African languages, exemplifying the literacy gains of multilingualism, as well as an increased articulation of indigenous knowledge. Multilingualism for one, provides a sense of local ownership, enhancing cultural and political assets, and, this "indigenous" effort at knowledge construction, will seemingly survive, because it is owned by local actors, founded on local economic, and social necessity.